“Gestión del talento humano y su incidencia en la calidad del servicio a los usuarios del gobierno autónomo descentralizado municipal del cantón El Empalme, año 2023” - Bravo Carranza, Jessica Jessenia (2024)
The present research work entitled “Human talent management and its impact on the quality of service to users of the decentralized municipal autonomous government of the El Empalme canton. Year 2023”, human talent is a strategic pillar in the success of institutions, having a team of qualified and motivated collaborators is vital for the success of any company. To achieve this, it is essential to apply human talent management, a process that allows retaining the best collaborators and increasing productivity. The main objective, which was: Evaluate the management of human talent and its impact on the quality of service to users. of the Municipal Decentralized Autonomous Government of the El Empalme canton, year 2023. The type of research was field and descriptive. The methods used were qualitative, quantitative and analytical. The population under study was 573 people (director of human talent, public officials and users). For this, interview instruments were applied that were applied to the director of human talent and a questionnaire guide that was applied to users and officials. The results obtained reflect that the regulations are met based on the institutional objectives, the workers do not feel motivated, the performance of the employees shows that it is necessary to improve some criteria such as incentives, training, to achieve efficient performance.